The Politics Of Survival: "Mutual Cunning" And The Machiavellian Ethos In Shakespeare's King Lear - Dr. Eleanor Vance (International Journal Of Literature And Languages, 2025)
Background Shakespeare’s King Lear is frequently analyzed for its profound exploration of justice, suffering, and familial collapse. While critical discourse has explored the play's political dimensions, it often focuses on the overt villainy of its antagonists. The influence and application of Niccolò Machiavelli's political philosophy in Renaissance drama provides a crucial, yet often narrowly applied, framework for understanding the brutal pragmatism that permeates the play's world. Purpose This article aims to demonstrate that Machiavellian tactics in King Lear are not confined to the villains but constitute a pervasive ethos of "mutual cunning" adopted by nearly all characters as a necessary tool for survival. We argue that the play presents a political landscape so thoroughly corrupted that even virtuous characters like Edgar and Kent are compelled to employ deception and strategic manipulation, thereby blurring the moral lines between hero and antagonist. Methodology Through a close reading of the Arden editions of King Lear [59, 60], this study applies a theoretical framework derived from Machiavelli's primary texts, The Prince [33] and The Discourses [32], along with contemporary scholarship on Machiavellianism in the Renaissance [47, 52]. The analysis focuses on the political strategies, rhetoric, and disguised actions of key characters, including Edmund, Goneril, Regan, Kent, and Edgar. Findings The analysis reveals that while Edmund, Goneril, and Regan are clear practitioners of Machiavellian realpolitik, the supposed heroes, particularly Edgar, become the play's most effective Machiavellian figures. Edgar's mastery of disguise and theatricality embodies the concept of virtù, allowing him to navigate and ultimately overcome the chaotic forces of fortuna. Conversely, King Lear's tragedy is framed as a failure of Machiavellian prudence, as he consistently makes politically disastrous decisions based on sentiment rather than strategic foresight. Conclusion Reading King Lear through the lens of mutual cunning reveals a deeply pessimistic political vision. The play suggests that in a world stripped of traditional order, the tools for survival and restoration are morally indistinguishable from those used for usurpation. This complicates the play’s final sense of justice and portrays a tragic reality where political efficacy requires the sacrifice of plain-dealing virtue.